2022
DOI: 10.3389/fmicb.2022.1031878
|View full text |Cite
|
Sign up to set email alerts
|

Gut-microbiome-based predictive model for ST-elevation myocardial infarction in young male patients

Abstract: BackgroundST-segment elevation myocardial infarction (STEMI) in young male patients accounts for a significant proportion of total heart attack events. Therefore, clinical awareness and screening for acute myocardial infarction (AMI) in asymptomatic patients at a young age is required. The gut microbiome is potentially involved in the pathogenesis of STEMI. The aim of the current study is to develop an early risk prediction model based on the gut microbiome and clinical parameters for this population.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…Nevertheless, whether gut microbiota participate in the initiation of AMI, some observational study reported the statistical correlation between gut bacteria profiling and AMI clinical phenotype. However, results are inconsistent across previous findings(15,16).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, whether gut microbiota participate in the initiation of AMI, some observational study reported the statistical correlation between gut bacteria profiling and AMI clinical phenotype. However, results are inconsistent across previous findings(15,16).…”
Section: Introductioncontrasting
confidence: 99%
“…Nevertheless, whether gut microbiota participate in the initiation of AMI, some observational study reported the statistical correlation between gut bacteria profiling and AMI clinical phenotype. However, results are inconsistent across previous findings (15,16). 4 So far, the reported investigations on the associations between intestinal microbes and AMI recruited mostly patients in the late or stable stage of AMI, sparse report on very early phase of disease has been shown.…”
Section: Introductionmentioning
confidence: 75%
“…Alterations in gut flora have been linked to several human diseases, including gastrointestinal disorders [ 103 ], ischemic stroke [ 104 ], allergies [ 105 , 106 ], inflammation [ 107 , 108 , 109 ], cancer [ 110 , 111 , 112 , 113 ] and cardiovascular disease [ 114 , 115 , 116 ]. For example, gut microbiota derangement is linked to ST-elevation myocardial infarction [ 117 ] and can be used in the setting of a relevant prediction model [ 118 ]. Thus, it is reasonable to search for gut microbiota alterations per se or its products as diagnostic disease biomarkers [ 119 , 120 , 121 ].…”
Section: Gut Microbiota As a Diagnostic Markermentioning
confidence: 99%
“…There has been a surge of interest in identifying the role of a new microbiome-dependent biomarker, trimethylamine N-oxide (TMAO). There is a known close relationship between elevated systemic levels of trimethylamine-N-oxide (TMAO) and an increased risk of adverse cardiovascular events, which allows the use of this biomarker as an indicator of the adequacy and prospects of therapy for myocardial infarction through changes in the intestinal microbiome [15][16][17][18]. Pro-and prebiotics and/or metabiotics are well known as means of targeted influence on the state of the intestinal microbiome, and in recent years plant polyphenols have also been considered as a microbiome corrector [19][20][21][22].…”
mentioning
confidence: 99%